DESIGN OF A PROTOTYPE OF PAPER MONEY DETECTOR FOR THE VIEW (Departement Information Systems Universitas Kebangsaan Republik Indonesia, 2023)
To access resources and information, use the library. The issue is that some libraries do not yet have a web-based online system for locating learning resources. Due to their inability to recognize and see money, blind persons are more likely to swap, misappropriate, or even defraud money during buying and selling operations. Designing a